Low thermal conductivity in La-filled cobalt antimonide skutterudites with an inhomogeneous filling factor prepared under high-pressure conditions. Issue 1 (7th December 2017) - Serrano-Sánchez, F.; Prado-Gonjal, J.; Nemes, N. M.; Biskup, N.; Varela, M.; Dura, O. J.; Martínez, J. L.; Fernández-Díaz, M. T.; Fauth, F.; Alonso, J. A.
Abstract : La-filled skutterudites with an inhomogeneous filling factor synthesized by high pressure exhibit a remarkably low lattice thermal conductivity. Abstract : La-filled skutterudites La x Co4 Sb12 ( x = 0.25 and 0.5) have been synthesized and sintered in one step under high-pressure conditions at 3.5 GPa in a piston-cylinder hydrostatic press. The structural properties of the reaction products were characterized by synchrotron X-ray powder diffraction, clearly showing an uneven filling factor of the skutterudite phases, confirmed by transmission electron microscopy. The non-homogeneous distribution of La filling atoms is adequate to produce a significant decrease in lattice thermal conductivity, mainly due to strain field scattering of high-energy phonons. Furthermore, the lanthanum filler primarily acts as an Einstein-like vibrational mode having a strong impact on the phonon scattering. Extra-low thermal conductivity values of 2.39 W m −1 K −1 and 1.30 W m −1 K −1 are measured for La0.25 Co4 Sb12 and La0.5 Co4 Sb12 nominal compositions at 780 K, respectively. Besides this, lanthanum atoms have contributed to increase the charge carrier concentration in the samples. In the case of La0.25 Co4 Sb12, there is an enhancement of the power factor and an improvement of the thermoelectric properties.